Friction stir extrusion of thin sheet stock. (April 2020) - Jarrell, Adam W.; Cui, Jeff; Strauss, Alvin M.; Cook, George E.
Abstract: A novel approach for applying Friction Stir Extrusion to thin sheet is tested to join AA6061 and steel. A dovetail geometry is formed in the steel through press dies, and aluminum is extruded to form an interlocking joint. Two transverse rates are tested, 50.8 mm/min and 76.2 mm/min, as well as two steel alloys, A36 and 4130. Sectioned into 6.35 mm samples, the welds failed through deformation between 280 N and 748 N. However, the 50.8 mm/min, A36 samples expressed an additional metal-to-metal bonding mechanism, increasing the strength to 1485 N. This research suggests unique geometries could improve the process.